2017
DOI: 10.1002/bmc.3966
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of wogonin, oroxylin a, schisandrin, paeoniflorin and emodin in rat serum by HPLC–MS/MS and application to pharmacokinetic studies

Abstract: Wogonin and oroxylin A in Scutellariae Radix, schisandrin in Chinensis Fructus, paeoniflorin in Moutan Cortex and emodin in Polygoni Cuspidate Rhizome et Radix are anti-inflammatory active compounds. A method for simultaneous determination of the five compounds in rat was developed and validated using high-performance liquid chromatography with tandem mass spectrometry (HPLC-MS/MS). The separation was performed on a Symmetry C column (4.6 × 50 mm, 3.5 μm) with acetonitrile and 0.1% formic acid aqueous solution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 25 publications
2
11
0
Order By: Relevance
“…UV Detection Wavelength for Schisandrin A and Schisandrin B The UV absorption of Schisandrin A and Schisandrin B is reported in a wide range between 210 to 250 nm. 8,16) In this work, wavelengths between 210-250 nm were compared for UV detection of Schisandrin A and Schisandrin B. The results showed that the detection sensitivity decreased with the wavelength increasing; 210 nm gave highest detection sensitivity.…”
Section: Optimization Of Separation Conditions For Schisandrin a And mentioning
confidence: 91%
See 1 more Smart Citation
“…UV Detection Wavelength for Schisandrin A and Schisandrin B The UV absorption of Schisandrin A and Schisandrin B is reported in a wide range between 210 to 250 nm. 8,16) In this work, wavelengths between 210-250 nm were compared for UV detection of Schisandrin A and Schisandrin B. The results showed that the detection sensitivity decreased with the wavelength increasing; 210 nm gave highest detection sensitivity.…”
Section: Optimization Of Separation Conditions For Schisandrin a And mentioning
confidence: 91%
“…Chromatographic methods are most commonly used for qualitative identification or quantitation of those natural dibenzocyclooctadiene lignans in raw herbal materials, and medicine or biological matrix samples. [6][7][8][9][10][11][12][13][14][15][16][17][18][19] In this work, a HPLC method was developed for separation and quantitation of Schisandrin A and Schisandrin B, with methanol-water as mobile phase, and UV detection. The present method was used to determine Schisandrin A and Schisandrin B in Huganpian Tablets sample.…”
Section: Introductionmentioning
confidence: 99%
“…The PK of baicalin, wogonoside, and oroxylin A glucuronide, showed obvious differences between administration as single herb (Huangqin-Tang) or as a compound prescription, with an increase in C max and AUC 0—lim , particularly for wogonoside [246]. In the PK analysis of a Chinese herbal mixture (Hu-gan-kan-kang-yuan capsule), the half-lives of wogonin and oroxylin A were much longer (around 40 h for both) than those reported in the literature, a difference probably also related to the influences of the other components of the formulation [247]. Co-administration of extracts from Scutellariae herba and Acacia catechu (L.f.) Willd.…”
Section: Intra-species Differences (Pk Variability)mentioning
confidence: 99%
“…Schizandrin (SCH, Figure 1(c)), which exhibited antioxidization, enhancing immunity, and antitumor effects, is a major bioactive lignan in Fructus Schisandrae Chinensis [14,15]. Up to now, some methods based on LC-MS or LC-MS/MS have been previously described to quantify PF, BBR, and SCH in the preparations or biological samples in other TCM formula or single herbs [16][17][18][19][20]. However, there is still no report on determining the three active ingredients simultaneously for content determination or pharmacokinetic investigations.…”
Section: Introductionmentioning
confidence: 99%